2020
DOI: 10.3389/fmicb.2020.00367
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Profiling Reveals the Effect of Breed on Active Rumen Eukaryotic Composition in Beef Cattle With Varied Feed Efficiency

Abstract: Exploring the compositional characteristics of rumen eukaryotic community can expand our understanding of their role in rumen function and feed efficiency. In this study, we applied metatranscriptomics to characterize the active rumen eukaryotic community (protozoa and fungi) in beef cattle (n = 48) of three breeds [Angus (AN), Charolais (CH), and Kinsella Composite (KC)] and with divergent residual feed intake (RFI). The composition of active rumen eukaryotic microbiota was evaluated based on enriched 18S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
1
17
1
Order By: Relevance
“…Most of the published studies focused on the rumen prokaryotes, emphasizing the importance of bacteria and archaea in affecting feed efficiency [ 8 , 47 , 52 ]. Rumen fungi play important roles in feed digestion [ 53 , 54 ], but few studies have focused on their linkage to feed efficiency [ 9 , 21 ]. Using metatranscriptomics, Zhang et al [ 9 ] characterized the rumen eukaryotic community in beef cattle and found significant differences in protozoa and fungi among animals with different feed efficiencies [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the published studies focused on the rumen prokaryotes, emphasizing the importance of bacteria and archaea in affecting feed efficiency [ 8 , 47 , 52 ]. Rumen fungi play important roles in feed digestion [ 53 , 54 ], but few studies have focused on their linkage to feed efficiency [ 9 , 21 ]. Using metatranscriptomics, Zhang et al [ 9 ] characterized the rumen eukaryotic community in beef cattle and found significant differences in protozoa and fungi among animals with different feed efficiencies [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rumen fungi play important roles in feed digestion [ 53 , 54 ], but few studies have focused on their linkage to feed efficiency [ 9 , 21 ]. Using metatranscriptomics, Zhang et al [ 9 ] characterized the rumen eukaryotic community in beef cattle and found significant differences in protozoa and fungi among animals with different feed efficiencies [ 9 ]. The lack of difference in the fungal community between the two cow groups in our study contradicts the above study on beef cattle, but concur with a previous metagenomic study on dairy cattle [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are plausible sources for the isolated urogenital trichomonads from the bovine GIT; Tetratrichomonas spp. (Zhang et al ., 2020 ), such as Te. buttreyi (Dufernez et al ., 2007 ), are known to inhabit the cattle gut, and P. hominis is known to occupy the GIT of a very wide range of animals (Li et al ., 2016 ), including cattle (Li et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These fungi may represent epiphytic fungal populations inhabiting forages and other feed components, and likely do not contribute directly to ruminal fermentation. However, in a recent study utilizing metatranscriptomic data to extract 18S rRNA genes [ 41 ], authors also detected members of the phyla Ascomycota and Basidiomycota in the rumen contents of cattle, and suggested that these fungi may play an active role in the scavenging of oxygen that enters the rumen during feed and water consumption. We identified eight distinct genera of the phylum Neocallimastigomycetes, including Neocallimastix, Caecomyces, Piromyces, Anaeromyces, Orpinomyces, Cyllamyces , and Buwchfawromyces in over 80% of the ruminal samples collected from steers on both baseline and alfalfa pasture.…”
Section: Discussionmentioning
confidence: 99%